Role of Indomie’s “Like No Other” Campaign in Cultivating Pester Power in the Children of Eleko Community, Lagos - Nnawuihe; Davina; Ogbu; U., S. (British Journal of Marketing Studies, 2019)
‘Pester power’ as a marketing strategy used in targeting kids has been a controversial topic for ages. Critics express concern over its negative results such as parent-child conflict, health hazards from unhealthy food consumption, unethical manipulation of children, etc. This births the question – who or what cultivates ‘pester power’ in children? While some scholars attribute the cultivation of pester power to advertisers, others suggest that the concept is a socially driven phenomena that has existed long before the coinage of the term. This study is an attempt to explore the concept of ‘pester power’ and determine the factors responsible for its cultivation in children by using Indomie’s “like no other” campaign as its focus. From the prisms of the Cognitive Development Theory and the AIDA Model, the study examined the processes of cultivating pester power in the early developmental stages of children in Eleko Community, Ibeju-Lekki, Lagos State. Exploratory research design comprising of both quantitative and qualitative methods was used for this investigation. Data was gathered from 244 questionnaires as well as interviews of five parents in the Eleko community. Results of the research revealed that Indomie “like no other” advertisement, parents and other identified factors played contributory roles in cultivating the children’s pester power. Based on these findings, the study recommends that parents should exercise better control over the exposure of their children to television and the communication patterns they create at home. The study makes the case for a stronger regulation of advertisement contents that target children as consumers and for further research on this sensitive subject matter.